Modeling and Comparative Analysis of PV Module with Improved Perturbation & Observation Based MPPT Technique for PV Applications - , Abhishek Kumar Gupta, Madhvi Gupta, Ravi Saxena (Archives of Current Research International, 2018)
Power-Voltage (P-V) characteristics of PV module are non-linear but it has a unique maximum power point. Maximum power point tracking (MPPT) techniques are used to maximise or to increase the output power of photovoltaic system for all time. These techniques give maximum output power, irrespective of the irradiation condition, temperature and electrical characteristics of loads. For the purpose of tracking the maximum power, MPPT techniques use some electronic converters. In this paper, an improved perturbation and observation (P&O) technique has been modeled and simulated in MATLAB/Simulink. The proposed technique is a modification of conventional P&O method. In the conventional P&O technique, the perturbations of the module operating point introduce with a fixed magnitude.